Introducing a new agility test in badminton - Kusuma, D. W. Y.; Raharjo, H. P.; Taathadi, M. S. (American Journal of Sports Science, 2015)
In every sport there are different agility demands, and agility measurement was supposed to be different. However, existing tools for measurement agility is considered not valid and reliable for measuring agility in badminton. The purpose of this study is to create agility test which is valid and reliable for badminton. For the purpose of this study, we recruited twenty students (10 badminton students of sport faculty and 10 professional badminton athletes, age range between 17 - 21 yr) by using R & D method. There are six stages; (1) analysis needed; (2) design; (3) prototype; (4) testing; (5) revision; and (6) validity and reliability of the test. Min K. Chin test was adopted to create a Badminton Agility Test (BAT) then inserted additional tools of computer software and hardware to facilitate the operation. Result of the quality and feasibility testing are: (1) the panel was slippery; (2) avoid confusion when start. The solutions of quality and feasibility are; (1) to replace the tread surface with non-slip material, rubber carpet is the most logical choice; (2) adding a sound signal when to start the test. The reliability value of BAT was 0.884, and validity of each item (rcount) were 0.864; 0.884; 0.869; 0.867; 0.858; 0.885; 0.862; 0.863. Statistical analysis revealed that the correlation coefficient is greater than the correlation coefficient table (r count > r table), suggesting that the BAT is reliable and valid to measuring badminton agility. Due to movement specificity, the BAT has significance for badminton agility assessment.